Reversed Crystal Growth: Implications for Crystal Engineering - Zhou, Wuzong (Advanced materials (Weinheim), 2010)
The discovery of reversed crystal growth routes in zeolite analcime and zeolite A implies that crystal growth does not always follow the classic theory established 100 years ago. Aggregation of nanoparticles may dominate in the early stages of crystal growth, followed by surface crystallization, and then extension from surface to core of the disordered aggregates. A perfect polyhedral morphology can be developed in a thin surface crystalline layer of a particle with a disordered core. Evidence of such a novel crystal growth phenomenon can be also found in many other materials. This article highlights the recent achievements in this topic, which might have a significant impact on crystal engineering, materials science, and mineralogy. The discovery of a reversed crystal growth route in zeolite analcime implies that crystal growth does not always follow classic theory. Aggregation of nanoparticles may dominate in early‐stage crystal growth, followed by surface crystallization, and then extension from surface to core. Recent developments and evidence of such a novel phenomenon in other materials are discussed.